KONFLIK SOSIAL ANTARA PENGENDARA OJEK ONLINE DENGAN PENGENDARA OJEK PANGKALAN DI CURUG, KELURAHAN BOJONGSARI KOTA DEPOK - Pratiwi, Aprilyanti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2017)
The phenomenon of online motorbike taxi versus ordinary motorbike taxi has become a new social conflict in Indonesian society. There is a disagreement between online motorbike taxi drivers and conventional motorbike taxi drivers. While conventional motorbike taxi drivers consider online motorbike drivers have taken their clients, the online motorbike taxi drivers do not think so. Online motorbike taxi drivers consider conventional motorbike taxi drivers as traditional people whom could not accept a new innovation. This new social conflict is interesting to be analysed because the problem is caused by the innovation. The purpose of this study is to understand how the social conflict between online motorbike taxi drivers with conventional motorbike taxi drivers in Depok, especially in the area of Curug, Bojongsari, Depok City. The method used in this research is descriptive qualitative with techniques data collection such as interviews, observation and document analysis. Interviews were conducted with three online taxibike and two ordinary taxibike. The results showed that the conflict is a group conflict between online motorbike taxi drivers and conventional motorbike taxi drivers. There is a competition between online motorbike taxi drivers and conventional motorbike taxi drivers. The latter feel threatened with the presence of online motorbike taxi drivers. This competition is not unresolved even enters a critical stage to the point it turned into a conflict.